Strobilanthes spathulatibracteata, a new species of Acanthaceae from northern Vietnam - Hai, Do Van; Thuy, Nguyen Thu; Lin, Zheli; Deng, Yunfei; Wan, Xia; Knapp, Ralf; Chen, De-Kui; He, Hai; Zhang, Li-Bing (Phytotaxa, 2023)
Strobilanthes spathulatibracteata is described as a new species from northern Vietnam. Morphologically, it resembles S. tonkinensis, but differs in its perennial undershrub habit, hirsute young stem, fragrant stem and blades, spathulate bracts and bracteoles with gland-tipped hirsute indumentum, 2-lipped calyx, 35–45 mm long corolla being puberulent outside and hirsute inside, and apically pubescent fruits. Photographs, illustrations, information on its habitat, ecology, pollen morphology and a preliminary conservation assessment are provided.